The Magnetic Field Dependence of Water T(1) in Tissues - Diakova, Galina (2011)
The magnetic field dependence of the composite (1)H(2)O NMR signal T(1) was measured for excised samples of rat liver, muscle, and kidney over the field range from 0.7 to 7 T (35 MHz to 300 MHz) with a NMR spectrometer using sample-shuttle methods. Based on extensive measurements on simpler component systems, the magnetic field dependence of T(1) of all tissues studied are readily fitted at Larmor frequencies above 1 MHz with a simple relaxation equation consisting of three contributions: a power law, A*ω(−0.60) related to the interaction of water with long-lived-protein binding sites, a logarithmic term B*τ(d)*log(1+1/(ωτ(d))(2)) related to water diffusion at macromolecular interfacial regions, and a constant term associated with the high frequency limit of water-spin-lattice relaxation. The parameters A and B include the concentration and surface area dependences respectively. The logarithmic diffusion term becomes significant at high magnetic fields and is consistent with rapid translational dynamics at macromolecular surfaces. The data are fitted well with translational correlation times of approximately 15 ps for human brain white matter, but with a B value three times larger than gray matter tissues. This analysis suggests that the water-surface translational correlation time is approximately three times longer than gray matter.